Radiodont frontal appendages from the Fezouata Biota (Morocco) reveal high diversity and ecological adaptations to suspension-feeding during the Early Ordovician - Potin, Gaëtan J.-M.; Gueriau, Pierre; Daley, Allison C. (Frontiers in Ecology and Evolution, 2023)
Introduction The Early Ordovician Fezouata Shale Formation (485–475Ma, Morocco) is a critical source of evidence for the unfolding Great Ordovician Biodiversification Event (GOBE), the largest radiation in animal diversity during the Paleozoic. The Fezouata Shale preserves abundant remains of ancient marine organisms, including hundreds of specimens of radiodonts, a diverse and globally distributed group of stem lineage arthropods that first appeared as raptorial predators during the Cambrian Explosion. Methods In this work, we study 121 radiodont frontal appendages from the Fezouata Shale. Frontal appendages are the most commonly preserved body parts of radiodonts, and their well-preserved anatomical characters are crucial for describing taxonomic diversity at the species level, while also providing essential data on mode of life, paleoecology, and feeding behaviour. Results Our data allow for a systematic review of suspension-feeding Hurdiidae radiodonts from Fezouata. The genus Pseudoangustidontus is recognised as a radiodont and ascribed to Hurdiidae, and a new second species of this genus is identified, Pseudoangustidontus izdigua sp. nov. Aegirocassis benmoulai is also reviewed and its diagnosis amended with new details of differentiated endites in this appendage. The morphological similarity between both genera allows us to erect Aegirocassisinae subfam. nov., which groups together the suspension-feeding hurdiids of the Fezouata Shale. Discussion Suspension-feeding radiodont appendages are more abundant than those of sediment sifting or raptorial radiodonts, with the Fezouata Shale showing the highest diversity of suspension-feeding radiodonts in the history of the group. This dominance and diversity of frontal filter-feeding appendages follows the “Ordovician Plankton Revolution”, which started in the upper Cambrian and saw a huge radiation in plankton diversity.